2014
DOI: 10.7150/jca.10238
|View full text |Cite
|
Sign up to set email alerts
|

Perineural Invasion and TAMs in Pancreatic Ductal Adenocarcinomas: Review of the Original Pathology Reports Using Immunohistochemical Enhancement and Relationships with Clinicopathological Features

Abstract: Objectives: Tumor-associated macrophages (TAMs) are thought to be involved in the perineural invasion (PNI) process and to be associated with poor prognoses. The associations between TAMs, PNI, and clinicopathological features in pancreatic ductal adenocarcinomas (PDAs) remain to be elucidated. Methods: Fifty-nine PDA patients who had undergone pancreaticoduodenectomy were retrospectively examined. The PNI statuses and TAMs were reviewed following H&E staining and S-100, CD68, and CD163 immunohistochemical sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 26 publications
(28 reference statements)
2
29
0
Order By: Relevance
“…We analyzed clinical outcomes in our PDA cohort (Supplementary Table 2) and observed a significantly higher proportion of PNI foci infiltrated by macrophages in patients who developed a local recurrence (Supplementary Fig. S12), a finding that supports prior work showing an adverse clinical impact of macrophage infiltration around nerves in PDA (5). To determine if macrophage-produced CTSB is relevant in promoting PNI by PDA in patients, we co-stained human PDA samples with anti-CD68 and anti-cathepsin B.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…We analyzed clinical outcomes in our PDA cohort (Supplementary Table 2) and observed a significantly higher proportion of PNI foci infiltrated by macrophages in patients who developed a local recurrence (Supplementary Fig. S12), a finding that supports prior work showing an adverse clinical impact of macrophage infiltration around nerves in PDA (5). To determine if macrophage-produced CTSB is relevant in promoting PNI by PDA in patients, we co-stained human PDA samples with anti-CD68 and anti-cathepsin B.…”
Section: Resultssupporting
confidence: 83%
“…Modern theories of PNI pathogenesis have placed significant focus on the role of the nerve microenvironment with PNI resulting from well-orchestrated interactions between cancer and the nerve (2, 3). While the cellular components of the nerve microenvironment are relatively static and well defined under homeostasis, PNI develops within a dynamic and complex tumor microenvironment that is enriched with immune cells recruited from the circulation (4, 5) and whose contribution to nerve invasion is unclear. Our knowledge gap in this area stems in part from the inability of in vitro PNI models to recapitulate the immune milieu, and the lack of consistent and quantifiable nerve invasion with current in vivo tumor models (6).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Up to date, this task has been accomplished using CD11c or NOS2 for M1 TAMs, and CD163, CD204, or CD206 for M2 TAMs. Indeed, increased M1 TAM densities seem to be associated with a favorable clinical outcome in NSCLC (Ma et al, 2010;Ohri et al, 2009), ovarian , colorectal (Edin et al, 2012), and gastric cancer (Zhang, Wang, et al, 2014a), while those of M2 are linked to poor prognosis in several tumors, including NSCLC (Hirayama et al, 2012;Ohtaki et al, 2010;Zeni et al, 2007), mesothelioma (Cornelissen et al, 2014), esophageal (Shigeoka et al, 2013), gastric cancer (Kawahara et al, 2010;Pantano et al, 2013), pancreatic (Hou et al, 2014;Ino et al, 2013;Kurahara et al, 2011;Sugimoto et al, 2014;Sugimura et al, 2015;Zeng et al, 2014), CRC (Herrera et al, 2013), HCC (Kong et al, 2013), Hodgkin lymphoma , renal (Dannenmann et al, 2013;Komohara et al, 2011;Xu et al, 2014), urothelial (Ichimura et al, 2014), breast (Medrek et al, 2012), endometrial (KĂŒbler et al, 2014), ovarian (Lan et al, 2013), melanoma ( Jensen et al, 2009), and squamous oral carcinoma . Additionally, some studies have demonstrated that, when associated with poor clinical outcome, CD68 + cells are often correlated with the tumor microvessel density, in addition to HIF, VEGF (Chai et al, 2008), and matrix metalloproteinase expression (Bolat et al, 2006;Hanada et al, 2000;Leek et al, 1996;Osinsky et al, 2011;Valković et al, 2002), suggesting that they might have an ...…”
Section: Role Of Tumor-associated Macrophagesmentioning
confidence: 97%